The Method of Using Information Technologies in Forming Professional Competences of Students of Technical Higher Education Institutions (Journal of Pedagogical Inventions and Practices, 2022)
The article examines the influence of information technology on the formation of professional competencies in students. The choice of technology will help improve the quality of elearning.